Adaptation, Association, and Analogy: Triple A of the Translator’s Decision-Making - Rebrii, Oleksandr; Demetska, Vladyslava (East European Journal of Psycholinguistics, 2020)
The article is dedicated to the analysis of concurrent verbalizations (also known as Think-Aloud Protocols, or TAPs) of semi-professional subjects of the introspective experiment based on the initial excerpt of Steven Brust’s fantasy novel The Desecrator. The research was conducted on the basis of activity-oriented approach within which translation is treated as an integrated cognitive process that unites perceptive, interpretative and productive operations. The participants of the experiment were students for Master’s Degree in Translation at the School of Foreign Languages of V. N. Karazin Kharkiv National University. The choice was determined by the fact that the subjects of this type have a high level of a foreign language competence as well as sufficient theoretical background in translation, while, at the same time, they lack practical experience which requires from them considerable psycho-cognitive and creative effort for decision-making in ambiguous situations. The aim of the research is to determine the role of adaptation, association and analogy in resolving problem situations in translation. Adaptation, association and analogy were highlighted as both psychological mechanisms and cognitive procedures of the translator’s decision-making. The psychological function of adaptation lies in bringing the translator to the state of adaptivity by applying available knowledge to new situations; its cognitive function lies in adjusting new or alien to the target audience concepts in accordance with the translator’s individual worldview. Psycho-cognitive function of association is twofold: firstly, the translator is expected to decipher and reproduce associations underlying the author’s decisions; secondly, the translator’s own decisions are often of associative nature. Analogical reasonings substantiate the translator’s choices through similarity-based heuristics, like those of representativeness and compatibility. The research allowed to expose some varieties of psycho-cognitive mistakes and to express the assumption that the translator’s erroneous decisions are ensued by the malfunctioning of the above mechanisms, i.e. by incorrect adaptations, associations, analogies.